A trimodular family 16 glycoside hydrolase from the cellulosome of Ruminococcus flavefaciens displays highly specific licheninase (EC 3.2.1.73) activity. Issue 7 (23rd July 2021) - Mondal, Sunetra; Thakur, Abhijeet; Fontes, Carlos M. G. A.; Goyal, Arun
Abstract : Cellulosomes are highly complex cell-bound multi-enzymatic nanomachines used by anaerobes to break down plant carbohydrates. The genome sequence of Ruminococcus flavefaciens revealed a remarkably diverse cellulosome composed of more than 200 cellulosomal enzymes. Here we provide a detailed biochemical characterization of a highly elaborate R. flavefaciens cellulosomal enzyme containing an N-terminal dockerin module, which anchors the enzyme into the multi-enzyme complex through binding of cohesins located in non-catalytic cell-bound scaffoldins, and three tandemly repeated family 16 glycoside hydrolase (GH16) catalytic domains. The DNA sequence encoding the three homologous catalytic domains was cloned and hyper-expressed in Escherichia coli BL21 (DE3) cells. SDS-PAGE analysis of purified His6 tag containing Rf GH16_21 showed a single soluble protein of molecular size 89 kDa, which was in agreement with the theoretical size, 89.3 kDa. The enzyme Rf GH16_21 exhibited activity over a wide pH range (pH 5.0–8.0) and a broad temperature range (50–70 °C), displaying maximum activity at an optimum pH of 7.0 and optimum temperature of 55 °C. Substrate specificity analysis of Rf GH16_21 revealed maximum activity against barley β-d -glucan (257 U mg −1 ) followed by lichenan (247 U mg −1 ), but did not show significant activity towards other tested polysaccharides, suggesting that it is specifically a β-1, 3-1, 4-endoglucanase. TLC analysis revealed that Rf GH16_21 hydrolyses barley β-d -glucan to cellotriose, cellotetraose and a higher degree of polymerization of gluco-oligosaccharides indicating an endo-acting catalytic mechanism. This study revealed a fairly high, active and thermostable bacterial endo-glucanase which may find considerable biotechnological potentials.